Combination of Xylanase and Bacillus Direct-fed Microbials, as an Alternative to Antibiotic Growth Promoters, Improves Live Performance and Gut Health in Subclinical Challenged Broilers - Nusairat , Basheer; McNaughton, James; Tyus, James; Wang, Jeng-Jie (International Journal of Poultry Science, 2018)
Objective: This study evaluated the effect of xylanase, Bacillus direct-fed microbials (DFM) and their combination on performance under a mild, subclinical challenge with two Eimeria species and Clostridium perfringens in broilers raised to 42 days. Materials and Methods: A total of 6 dietary treatments were used throughout the trial. Diets were supplemented with one of the following; no xylanase or Bacillus (control), xylanase only, Bacillus L. only, Bacillus A. only, xylanase plus Bacillus L. or xylanase plus Bacillus A. Data were analyzed as randomized complete block design. Results: When compared to control at 42 days, the xylanase, Bacillus L. and Bacillus A. improved (p<0.05) BW gain by 93, 94 and 53 g, respectively and FCR by 4, 4 and 6 points, respectively. When compared to control at 42 days, the combination of xylanase and Bacillus L. or Bacillus A. improved (p<0.05) BW gain by 142 or 147 g, respectively and FCR by 9 or 11 points, respectively. The combination of xylanase and Bacillus L. or Bacillus A. reduced (p<0.05) BW coefficient of variation from 15.09% (control) to 8.27 or 8.22%, respectively at 42 days. The combination of xylanase and Bacillus L. or Bacillus A. reduced (p<0.05) gross lesion scores in small intestine and C. perfringens count at 42 days compared to control. Conclusion: Results suggest that xylanase and Bacillus alone may improve broiler performance and reduce the severity of intestinal lesions due to Eimeria and C. perfringens challenges and that the effect of xylanase and Bacillus DFM are additive.